Fault-Diagnosis Applications Model-Based Condition Monitoring: Actuators, Drives, Machinery, Plants, Sensors, and Fault-tolerant Systems - Isermann, Rolf.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Supervision, condition-monitoring, fault detection, fault diagnosis and fault management play an increasing role for technical processes and vehicles in order to improve reliability, availability, maintenance and lifetime. For safety-related processes fault-tolerant systems with redundancy are required in order to reach comprehensive system integrity.  This book is a sequel of the book ?Fault-Diagnosis Systems? published in 2006, where the basic methods were described. After a short introduction into fault-detection and fault-diagnosis methods the book shows how these methods can be applied for a selection of 20 real technical components and processes as examples, such as: Electrical drives (DC, AC) Electrical actuators Fluidic actuators (hydraulic, pneumatic) Centrifugal and reciprocating pumps Pipelines (leak detection) Industrial robots Machine tools (main and feed drive, drilling, milling, grinding) Heat exchangers Also realized fault-tolerant systems for electrical drives, actuators and sensors are presented. The book describes why and how the various signal-model-based and process-model-based methods were applied and which experimental results could be achieved. In several cases a combination of different methods was most successful. The book is dedicated to graduate students of electrical, mechanical, chemical engineering and computer science and for engineers.
1 Introduction -- Part I Supervision, Fault Detection and Diagnosis 2 Supervision, fault-detection and diagnosis methods - a short introduction -- Part II Drives and Actuators 3 Fault diagnosis of electrical drives -- 4 Fault diagnosis of electrical actuators -- 5 Fault diagnosis of fluidic actuators Part III Machines and Plants 7 Leak detection of pipelines -- 8 Fault diagnosis of industrial robots -- 9 Fault Diagnosis of machine tools -- 10 Fault detection of heat exchangers Part IV Fault-tolerant Systems 11 Fault-tolerant systems - a short introduction -- 12 Examples of fault-tolerant systems Part V Appendix 13 Appendix -- References -- Index.
Keywords: Electronic books; Engineering; Computer science; Systems theory; System safety; Control, Robotics, Mechatronics; Quality Control, Reliability, Safety and Risk; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences; Computer Applications; Systems Theory, Control